A spectroscopic study of the influence of CuO addition on the ZnO-TeO2 glass and glass ceramics - Stefan, Razvan; Karabulut, Mevlut; Popa, Adriana; Culea, Eugen; Bolundut, Liviu; Olar, Loredana; Pascuta, Petru (Elsevier Science Bv, 2018)
As cast and heat treated samples in the xCu(100-x)[ZnO center dot 2TeO(2)] system with 0 <= x <= 20 mol% were prepared and investigated by X-ray diffraction, electron paramagnetic resonance (EPR), UV-VIS and infrared (IR) spectroscopies. The as cast samples were vitreous while the heat treated ones became crystalline. For the heat treated samples, the main crystalline phase is the Zn2Te3O8. Increasing the CuO content of these samples up to x = 10 mol% produce the occurrence of zinc tellurium oxide and copper telluride crystalline phases. For x = 20 mol% CuO the sample contains a mixture of phases, namely copper telluride, zinc tellurium oxide and tellurium copper oxide. EPR data show the presence of the Cu2+ ions located at sites with an axially distorted octahedral symmetry, as both isolated and coupled species. These data offer information concerning the evolution of the reduction of Cu2+ to Cu+ during the melting of samples. UV Vis data support the assumption concerning the presence of copper ions in the two mentioned valence states. The IR data suggest that increasing the copper content of samples determines the breaking of Te-O bonds from both TeO4 and TeO3 structural units while for the heat treated samples increases the structural disorder and the degree of deformation of the basic structural units.
Keywords: Optical-Properties; Tellurite Glasses; Absorption; Transition; Ions